The influence of career planning towards insurance agents' strategy for career satisfaction - Tan, Fee Yean; Yahya, Khulida Kirana (World Business Institute, Australia, 2011)
This research reports on the influence of career planning and career strategy on insurance agents' career satisfaction.A total of 531 full-time insurance agents located in the Northern states of Peninsular Malaysia participated in this research. Using hierarchical multiple regression,researchers found that awareness of self and environment were positively related to career strategy and career satisfaction.Goal-setting had a positive relationship with career strategy and a negative influence on career satisfaction.The results further indicated that career strategy partially mediates the relationship between awareness of self and environment and career satisfaction. The theoretical and practical implications of these findings were also discussed.